Adolescent relational roots of adult blood pressure: A 14-year prospective study. (24th December 2022) - Allen, Joseph P.; Loeb, Emily L.; Tan, Joseph; Davis, Alida A.; Uchino, Bert
Abstract: Intensity in adolescent romantic relationships was examined as a long-term predictor of higher adult blood pressure in a community sample followed from age 17 to 31 years. Romantic intensity in adolescence – measured via the amount of time spent alone with a partner and the duration of the relationship – was predicted by parents' psychologically controlling behavior and was in turn found to predict higher resting adult systolic and diastolic blood pressure even after accounting for relevant covariates. The prediction to adult blood pressure was partially mediated via conflict in nonromantic adult friendships and intensity in adult romantic relationships. Even after accounting for these mediators, however, a direct path from adolescent romantic intensity to higher adult blood pressure remained. Neither family income in adolescence nor trait measures of personality assessed in adulthood accounted for these findings. The results of this study are interpreted both as providing further support for the view that adolescent social relationship qualities have substantial long-term implications for adult health, as well as suggesting a potential physiological mechanism by which adolescent relationships may be linked to adult health outcomes.